Talking about culturally responsive approaches to education: teacher professional learning, Indigenous learners and the politics of schooling - Bishop, Michelle; Vass, Greg (The Australian Journal of Indigenous Education, 2020)
Abstract Culturally responsive approaches to schooling (CRS) aim to address pervasive inequities that exist in education. More specifically, CRS practices seek to improve the experiences and academic achievements of marginalised and minoritised learners, such as those from culturally and linguistically diverse backgrounds. In this paper, we consider the possibilities for CRS in the context of Australia where Indigenous students (along with their parents, peers and teachers) are consistently reminded, courtesy of the deficit government policies and ‘close the gap’ rhetoric, that they have the worst educational outcomes of any settler society. This paper does not seek to offer fixed solutions in response to this. Rather, based on shared experience researching and teaching together that draw on CRS, the paper foregrounds a collaborative culturally responsive dialogue between the authors. Together we discuss, deliberate and despair about the state of the education system for Indigenous students, we also remain tentatively hopeful about how CRS might become embedded in teaching and learning, through teacher professional learning, in ways that are relevant to the Australian context.